Coenzyme Q10 Phytosome Formulation Improves CoQ10 Bioavailability and Mitochondrial Functionality in Cultured Cells - Nicola Rizzardi; Irene Liparulo; Giorgia Antonelli; Francesca Orsini; Antonella Riva; Christian Bergamini; Romana Fato (Antioxidants, 2021)
Coenzyme Q10 (CoQ10) is a lipid-soluble molecule with a dual role: it transfers electrons in the mitochondrial transport chain by promoting the transmembrane potential exploited by the ATPase to synthesize ATP and, in its reduced form, is a membrane antioxidant. Since the high CoQ10 hydrophobicity hinders its bioavailability, several formulations have been developed to facilitate its cellular uptake. In this work, we studied the bioenergetic and antioxidant effects in I407 and H9c2 cells of a CoQ10 phytosome formulation (UBIQSOME®, UBQ). We investigated the cellular and mitochondrial content of CoQ10 and its redox state after incubation with UBQ. We studied different bioenergetic parameters, such as oxygen consumption, ATP content and mitochondrial potential. Moreover, we evaluated the effects of CoQ10 incubation on oxidative stress, membrane lipid peroxidation and ferroptosis and highlighted the connection between the intracellular concentration of CoQ10 and its antioxidant potency. Finally, we focused on the cellular mechanism that regulates UBQ internalization. We showed that the cell lines used in this work share the same uptake mechanism for UBQ, although the intestinal cell line was less efficient. Given the limitations of an in vitro model, the latter result supports that intestinal absorption is a critical step for the oral administration of Coenzyme Q10 formulations.